Tuntaskan Aspirasi Masyarakat Melalui Kegiatan KKN Pramuka: Peningkatan Kualitas Hidup dan Keberlanjutan Lingkungan - Fernandes, Feri; Sumantri, Ajis (Jurnal Kewirausahaan dan Bisnis, 2024)
Community Service Program (Kuliah Kerja Nyata or KKN) with the theme of Scouts aims to improve the quality of life in the community and support environmental sustainability. Through various social service activities such as life skills coaching, entrepreneurship training, and economic empowerment programs, Scout KKN students have successfully made a significant positive impact on community welfare. In addition, environmental preservation efforts are also a primary focus, involving tree planting, waste management, and education on environmentally friendly practices. With a holistic approach, Scout KKN not only provides short-term benefits but also creates sustainable positive impacts, reflecting the spirit of mutual cooperation, togetherness, and sustainability in building a better community.